Inhibition of receptor-interacting protein kinase 1 improves experimental non-alcoholic fatty liver disease - Majdi, Amine (2020)
In non-alcoholic fatty liver disease (NAFLD), hepatocytes can undergo necroptosis: a regulated form of necrotic cell death mediated by the receptor-interacting protein kinase (RIPK) 1. Herein, we assessed the potential for RIPK1 and its downstream effector mixed lineage kinase domain-like protein (MLKL) to act as therapeutic targets and markers of activity in NAFLD.